Kinetika Reaksi Demineralisasi Pada Isolasi Kitin Dari Limbah Ebi - Yesi Afriani; Ahmad Fadli; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Chitin is a biopolymer, used for various fields like cosmetics, biomedical, porous material, absorbent of heavy metal, and dietary. The synthesized of chitin from ebi’s waste by deproteinization and demineralization process was investigated. The aims of this research is to determine the reaction kinetics of demineralization at isolation of chitin with variables of concentration of HCl and stirring rate. The research was started by mixing ebi’s waste powder with HCl concentration of 0,2 N; 0,6 N; 1 N; 1,4 N; and 1,8 N at temperature 29°C and the stirring rate 50, 100, 150, 200, and 250 rpm in the beaker glass and completely with stirrer. The Samples were taken for 15, 25, 35, 45 and 60 minutes in amount 20 mL, then washed until neutral and filtered by a filter paper. Isolated chitin was destructed by H2SO4 and HNO3 to determine calcium carbonate content by titration of complexometry. The results show that reaction kinetic follows pseudo second order equation. Reaction rate constant increases with increasing concentration. The reaction rate in the concentration 0,2 N; 0,6 N; 1 N; 1,4 N; and 1,8 N and stirring rate 150 rpm increased from 0,003 to 0,404 min-1. But stirring rate undefined by approaching of kinetics homogenous reaction. The Range of reaction rate constant is 0,00167- 0,394 min-1.Keywords : biopolymer, chitin, demineralization, ebi’s waste, reaction kinetic.